The Essential Role of Distance Learning Technology in the Development of Higher Education - Tilaev Ermat Rakhmatovich (Zien Journals, 2022)
This article discusses the impact of distance learning on the quality and effectiveness of distance learning in the higher education system, the development of new technical means of distance learning and its widespread use in the educational process, in particular, the development of partnerships with foreign scholars. to enable users to study in a voluntary educational institution anywhere in the world, regardless of their place of residence, to improve the quality of education based on the professional potential of professors and teachers in educational institutions, to create opportunities for continuous education for users, to bring different forms of education closer together issues have been interpreted..
Keywords: education; system; process; tool